Cross talk between spliceosome and microprocessor defines the fate of pre‐mRNA. (30th April 2014) - Mattioli, Chiara; Pianigiani, Giulia; Pagani, Franco
<x xml:space="preserve">Abstract</x> The spliceosome and the microprocessor complex (MPC) are two important processing machineries that act on precursor (pre)‐mRNA. Both cleave the pre‐mRNA to generate spliced mature transcripts and microRNAs (miRNAs), respectively. While spliceosomes identify in a complex manner correct splice sites, MPCs typically target RNA hairpins (pri‐miRNA hairpins). In addition, pre‐mRNA transcripts can contain pri‐miRNA‐like hairpins that are cleaved by the MPC without generating miRNAs. Recent evidence indicates that the position of hairpins on pre‐mRNA, their distance from splice sites, and the relative efficiency of cropping and splicing contribute to determine the fate of a pre‐mRNA. Depending on these factors, a pre‐mRNA can be preferentially used to generate a miRNA, a constitutively or even an alternative spliced transcript. For example, competition between splicing and cropping on splice‐site‐overlapping miRNAs (SO miRNAs) results in alternative spliced isoforms and influences miRNA biogenesis. In several cases, the outcome of a pre‐mRNA transcript and its final handling as miRNA or mRNA substrate can be frequently closely connected to the functional relationships between diverse pre‐mRNA processing events. These events are influenced by both gene context and physiopathological conditions. WIREs RNA 2014, 5:647–658. doi: 10.1002/wrna.1236 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.